1986
DOI: 10.1111/j.1467-8624.1986.tb00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Automaticity, Retrieval Processes, and Reading: A Longitudinal Study in Average and Impaired Readers

Abstract: In this longitudinal investigation, the development of word-retrieval speed and its relationship to reading was studied in 72 average and 11 severely impaired readers in the kindergarten to grade 2 period (5-8 years). Subjects received a battery of 3 reading measures and 4 continuous naming tests with varied stimulus requirements. Results indicated that the relationship of retrieval speed to reading is a function of development and the correspondence between higher- and lower-level processes in the specific re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(40 citation statements)
references
References 22 publications
3
37
0
Order By: Relevance
“…Rapid automatized naming is commonly impaired in children and adults with dyslexia and was reported to be one of the main precursors of later reading ability in children (De Jong and Van der Leij, 1999; Kirby et al, 2003; Kobayashi et al, 2005; Wolf, 1986; Wolf et al, 1986). Furthermore, previous research reported significant correlations between gray matter volume in a left occipitotemporal region and digit naming (Kronbichler et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid automatized naming is commonly impaired in children and adults with dyslexia and was reported to be one of the main precursors of later reading ability in children (De Jong and Van der Leij, 1999; Kirby et al, 2003; Kobayashi et al, 2005; Wolf, 1986; Wolf et al, 1986). Furthermore, previous research reported significant correlations between gray matter volume in a left occipitotemporal region and digit naming (Kronbichler et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the average of GMVIs within each ROI for the whole experimental group ( n =20; 10 FHD+/10 FHD–) was correlated with standardized behavioral measures, which have shown to predict reading ability: phonological processing (e.g. Flax et al, 2008; Gallagher et al, 2000; Pennington and Lefly, 2001; Puolakanaho et al, 2008; Scarborough, 1990; Snowling et al, 2003;) and RAN (De Jong and Van der Leij, 1999; Kirby et al, 2003; Kobayashi et al, 2005; Wolf, 1986; Wolf et al, 1986). Statistical correlation analysis was performed using SPSS software package, version 16.0 (SPSS Inc., 1999).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, all theories are consistent in the basic information processing steps required for performing the rapid serial naming task, collectively termed lexical access . Namely, lexical access during rapid naming requires that the participant rapidly transfer presented visual symbols to phonological codes retrieved from long term memory store (Denckla & Rudel, 1974; Wagner & Torgesen, 1987; Wolf, Bally, & Morris, 1986). At issue, however, is just how much variability in reading is attributed to the lexical access process.…”
Section: Introductionmentioning
confidence: 99%
“…The latter view received support from a genetically informed study by Naples, Chang, Katz, and Grigorenko (2009), who found that RAN and PA, assessed in a large sample of unselected families, had only partially overlapping genetic etiology; i.e., each skill involved both shared and unique genes, consistent with the two being non-redundant contributors to reading ability. According to this view, RAN skills and reading are related because both require rapid sequencing of visually presented information and integration of visual recognition with lexical retrieval (e.g., Wolf, Bally, & Morris, 1986, Bowers & Wolf, 1993; Wolf & Bowers, 1999). In line with this view, there is ample evidence that RAN contributes to reading above and beyond PA and pSTM (e.g., Cardoso-Martins & Pennington, 2004; Clarke, Hulme, & Snowling, 2005; Compton, Defries, & Olson, 2001, but cf.…”
mentioning
confidence: 99%